Des Wahlvolks großer Auftritt.: Wahlritual und demokratische Kultur in Italien und Westdeutschland nach 1945 - Gatzka, Claudia Christiane (Comparativ, 2013)
After fascism, Italians and Germans proved themselves enthusiastic voters in the newly established democratic setting. The article investigates the local practices regarding the ballot by focusing on the performative character of voting which reveals notions of the state, the local and the individual, of political parties and political conflict: notions that shaped the specific democratic cultures in Italy and Germany. Reading the voting practices through the lens of these issues, it is argued that the importance of polling in the two post-fascist societies derived from different social and political meanings inherent to the act of the vote. Nevertheless, in both countries these meanings helped to establish a democratic tradition that promoted voting attendance as a sign of belonging to the local community of ‘good democrats’.